Alterations induced by juvenile obesity on the renal tissue of nutrient restricted offspring - Fainberg, Hernan Pablo (2010)
Human epidemiological studies have indentified obesity as an independent risk factor for renal disease. In addition, maternal nutrient restriction (MNR) during gestation results in a series of adaptations that may predispose those offspring to obesity and hypertension. Recent reports demonstrated that obese sheep exposed to MNR during early to mid gestation have a predisposition to ectopic lipid deposition in the heart and a rise in necrotic adipocytes, which are markers of severe metabolic dysfunction. Surprisingly, in this model of MNR, the renal tissue of those offspring showed an apparent reduction in cell apoptosis. However, renal diseases associated with obesity have a slow progression and their mechanisms are not completely understood. In the light of these results, the main hypothesis of my thesis is that the renal amelioration observed in those nutrient restricted (NR) obese offspring is a product of post-injury responses, inducing scarring and others adaptations to obesity. Therefore, some of the main regulatory factors in renal and perirenal adipose tissue (PAT) development were analysed in seven-day-old and one-year-old obese sheep offspring exposed to MNR (3.5 KJ/days) from 30 to 80 gestational days (term ≈ 145 days).